The genus Neoromicia (Family Vespertilionidae) in Madagascar, with the description of a new species - Goodman, Steven M.; Taylor, Peter J.; Ratrimomanarivo, Fanja; Hoofer, Steven R. (Zootaxa, 2012)
Using molecular genetics, male sexual organ morphology (baculum), and cranio-dental characters, we describe a new spe-cies of the genus Neoromicia from Madagascar, N. robertsi sp. nov. It is presumed to be endemic to the island and isknown from three specimens taken in montane areas of the eastern central region. The new species shows 1.0 % and 2.8%divergence in the 12S rRNA and 16S rRNA genes, respectively, from its nearest congener and is notably larger in cranio-dental measurements than other members of the genus occurring on Madagascar. This new species was previously iden-tified as N. melckorum, which is considered a junior synonym of southern African N. capensis. Neoromicia malagasyen-sis, an endemic to central western Madagascar, is the sister species to N. robertsi and the two are best considered vicariantspecies. Specimens provisionally assigned to N. malagasyensis, but notably smaller in baculum and skull size, and withdifferent baculum morphology, probably represent another unknown species from the island. Given the apparent rarity ofN. robertsi compared with other Malagasy members of this genus living in the eastern portion of Madagascar, it is considered a taxon of conservation concern.